The Space Dimension of Jordanian Penal Code Comparative Study with French legislation - Rana Atour (My University, 2011)
The application of penal law of states is normally bordered on its land, the crimes that fells on its (land, sea, or air). But sometimes it can be applied on other crimes outside for some considerations such as relating with one of its citizens or for its importance or avoiding evasion of a criminal. Legislations differs from one state to another of the Domain that it gives to its legislation to be applied in the place. Certes, this study lightens the domain of Jordanian penal law in the place, comparative study with French Legislations.

يتحدد تطبيق القانون الجنائي لدول معينة ضمن نطاق مكاني محدد عادة ما يكون على أراضيها أي على الجرائم الواقعة ضمن سيادتها من ارض وبحر وجو. ولكن من المكن ان تمتد قواعد القانون الجنائي لتطبق على جرائم مرتكبة خارج أراضيها لاعتبارات معينة قد تتعلق بأحد مواطنيها أو مصالحها أو لعدم افلات مجرم من العقاب، وتختلق التشريعات الجنائية في مدى توسيع نطاق قانونها من حيث المكان، ومن هنا جاءت هذه الدراسة لتركز على البعد المكاني لقانون العقوبات الأردني مقارنة مع التشريع الفرنسي.
البعد المكاني لقانون العقوبات الأردني دراسة مقارنة مع التشريع الفرنسي